CHLOROPLAST DNA VARIATION IN COCONUT IS OPPOSITE TO ITS NUCLEAR DNA VARIATION - Lalith Perera (International Coconut Community Journal, 2002)
The pattern of world distribution of two major fruit morphotypes of coconuts has led to development of theories on origin, domestication and dissemination of coconut. Results of recent nuclear DNA analyses are in agreement with these theories with several other new insights. Compared to the plant nuclear genome however, the plant organelle genomes, the chloroplast genome and the mitochondrial genome are highly conserved and are maternally inherited in most angiosperms. Therefore, most useful information have come from regions of DNA located in organelle genome for studying phylogeny in angiosperms and for deducing historical information and evolutionary history of populations such as past migration routes and colonization dynamics. This study was aimed to determine the feasibility of developing polymorphic cytoplasmic markers, particularly the chloroplast markers. Chloroplast DNA variation of coconut from all coconut growing regions in the world assessed by both restriction digestions and physical separation of PCR products obtained with universal primers, by chloroplast microsatellites and by sequencing showed no variation. This tends to suggest that coconut may have gone through a severe cytoplasmic bottleneck and only one chloroplast type may have participated in the colonization process.